BIMBINGAN BAGI GURU DALAM UPAYA MENANGANI KASUS BULLYING DI SEKOLAH SMP NEGERI 40 BANDAR LAMPUNG TAHUN PELAJARAN 2019/2020 - Tanod, Mareyke Jessy; Murni, Sri (Jurnal Inspirasi Bimbingan dan Konseling (JGCI), 2020)
More years of bullying behavior is increasing both verbally, physically and psychologically. Bullying is an act of intimidation by a stronger party against a weaker party. One factor of bullying behavior is low empathy. The purpose of this study was to find out whether there are differences in bullying behavior on single sex school type and coeducational schools after being controlled by empathy. The method used in this study is quantitative ancova test, with the scale of bullying behavior and empathy scale Interpersonal Reactivity Index (IRI) The number of subjects as much as 385 female santri with cluster random sampling technique.The results showed the differences in bullying behavior in the type of school single sex school And coeducational school after being controlled by empathy significance value of 0.001 (P â‰¤ 0.05 = 0.001 â‰¤ 0.05) . In addition, the contribution of empathy control to bullying behavior is only 3.3%. The rest is influenced by other factors not explained to the authors in this study